ANALISIS KEMAMPUAN BERPIKIR KREATIF DITINJAU DARI ADVERSITY QUOTIENT PADA PEMBELAJARAN CREATIVE PROBLEM SOLVING PENDEKATAN OPEN-ENDED - Windarti, Desti Hana; Wardono, Wardono; Mariani, Scolastika (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research aims to determine the quality of creative mathematical thinking abilities in terms of AQ in CPS learning with an open-ended approach assisted by G. Classroom. The type of research is quantitative research. The research population was all class VII. The research sample used a cluster random sampling technique. The conclusions of the results of the analysis were: (1) the mathematical creative thinking ability of participants who received the CPS learning model with an open-ended approach assisted by Google Classroom achieved BTA (2) Students with the ability to think creatively mathematically in terms of AQ in CPS learning with an open-ended approach assisted with Google classroom achieves learning completeness of more than 75%, (3) the mathematical creative thinking ability in the CPS learning model with the open-ended approach assisted by G. Classroom is better than the PBL learning model, (4) the proportion of mathematical creative thinking ability completeness in the CPS learning model approach open-ended with the help of Google Classroom is more than the proportion of students in the PBL learning model, (5) there is a difference in the average increase in mathematical creative thinking abilities of students in the CPS learning model with the open-ended approach assisted with G. Classroom and students in the PBL learning model, (6) There is a positive influence on the adversity quotient on the ability to think creatively mathematically in mathematics learning